Comparative Analysis of the Bacterial Membrane Disruption Effect of Two Natural Plant Antimicrobial Peptides - Farkas, Attila; Maróti, Gergely; Kereszt, Attila; Kondorosi, Éva (Frontiers in Microbiology, 2017)
In the Medicago truncatula genome about 700 genes code for cysteine-rich (NCR) small peptides that are expressed in the symbiotic organ, the root nodule, where they control terminal differentiation of the endosymbiotic rhizobium bacteria to nitrogen-fixing bacteroids. Cationic NCR peptides were predicted to have antimicrobial activities. Here antibacterial activities of NCR247, NCR335, polymyxin B and streptomycin were investigated and compared on two foodborne pathogens Salmonella enterica and Listeria monocytogenes as representatives of Gram-negative and Gram-positive bacteria. The integrity of the bacterial membrane was seriously compromised by these NCR peptides. Different localization was observed for NCR247 and NCR335 in the treated bacteria, the peptides mostly accumulated in the cytosol in S. enterica while they remained in the bacterial membrane in L. monocytogenes. Scanning electron microscopy revealed distinct membrane morphology of the peptide-treated bacteria. Complete cell disruption was induced by polymyxin B and NCR335 in S. enterica while NCR247 treatment resulted in extensive budding observed on the cell surface of Salmonella. Polymyxin B had no effect on L. monocytogenes while NCR335 and NCR247 provoked morphological changes on this bacterium, the whole Listeria cell content was released in response to NCR335 treatment.